Literature Review: Potensi Monascus Purpureus sebagai Agen Antikolesterol Alami - Saeful Amin; Hanif Azhar Zaidaan; Rayhanah Firdaus Kusmawan (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Monascus purpureus, also known as red yeast rice, is a red mold widely used in traditional Asian food fermentation, particularly in Indonesia and China. One of its main bioactive compounds is monacolin K, a substance structurally identical to lovastatin, a well-known cholesterol-lowering statin drug. Monacolin K works by inhibiting the HMG-CoA reductase enzyme, a key enzyme in the biosynthesis of cholesterol in the liver. Various modern studies have demonstrated that Monascus purpureus consumption can significantly reduce total cholesterol, low-density lipoprotein (LDL), and triglyceride levels, while increasing high-density lipoprotein (HDL) levels, with relatively minimal side effects compared to synthetic statins. In addition, the natural pigments produced by Monascus purpureus, such as monascin and ankaflavin, exhibit strong antioxidant and anti-inflammatory activities that help protect vascular endothelial cells from oxidative stress and inflammation—two major factors contributing to atherosclerosis. The combination of M. purpureus extracts with probiotics or other natural ingredients, such as garlic or fermented soy products, has also been shown to produce synergistic effects in improving lipid metabolism and promoting cardiovascular health. With its potent bioactive components and high safety profile, Monascus purpureus holds great potential to be developed as a natural anticholesterol agent for the prevention and management of dyslipidemia in a sustainable and effective manner.